Pemahaman Hadits Larangan Menerima Upah Dalam Mengajarkan Al-Qur’an - Tatan Setiawan; Muhammad Zainul Hilmi; Reza Pahlevi Dalimunthe (Jurnal Iman dan Spiritualitas, 2021)
This article discusses the understanding of the hadith on the prohibition of receiving wages in teaching the Al-Quran. The form of appreciation given to teachers from students, both in the form of gifts and rewards in teaching Al-Qur'an, has become a dispute of opinion among the scholars. This study is very important to discuss to find out the similarities and differences in opinion of the scholars of fiqh schools regarding the hadith of the prohibition. The writing of this article uses a literature-based comparative study methodology equipped with hadiths that serve as a reference as a basis for opinion among scholars of fiqh schools. This article concludes that classical scholars from the Hanafi school and scholars from the Hambali school forbid accepting wages for teaching the Koran, while scholars from the Maliki school of thought, scholars from the Shafi'i school of thought, and contemporary scholars from the Hanafi and Madzhab schools Hambali allows receiving rewards for teaching the Qur'an according to certain circumstances.